Coconut Harvesting Habitus and Community Plantation Production on Simeuelue Island - Nasution, Abdullah Akhyar; Iromi Ilham; Halim Akbar; Nasrul Huda; Destriana Wulandari; Kudussisara; Muh. Fahruddin Alawi (Demeter: Journal of Farming and Agriculture, 2024)
The people of Simeulue Island, Aceh, have a long-standing tradition of coconut gardening. Before the 2004 earthquake and tsunami, coconut production in this area was quite high. However, in recent years, the decline in coconut production has threatened the supply of raw materials for the local processing industry. As a result, hundreds of tons of raw materials must be imported from Nias Island to meet the needs of the industry. One of the main causes of this decline is suboptimal harvesting practices. This study revealed that most coconut varieties cultivated in Simeulue are Kelapa Dalam, which has a productive age of 10 and 30 years. Based on visitation patterns, there are two types of coconut gardens: those that are regularly visited and those that are rarely visited. The rarely visited gardens are only visited during harvest time, about once every three months. The vegetation in these gardens tends to be denser, but their productivity is difficult to control. Most of the productive coconuts currently come from low-quality seeds, namely small coconuts that are not harvested because they are considered uneconomical. These seeds are often less than 1 kg; some are as big as 250 ml mineral water bottles. Efforts are needed to ensure the sustainability of the coconut industry in Simeulue; efforts are needed to provide superior seeds that can improve the quality and quantity of future harvests.